ANALYSIS OF CATCH QUOTA POLICY IN THE UTILIZATION OF FISHERY RESOURCES IN PASURUAN DISTRICT OF EAST JAVA - Wildan Alfarizi; Guntur Guntur; Amin Setyo Laksono (Fakultas Perikanan dan Kelautan, Universitas Riau, 2019)
This study was aimed to this study was conducted to determine the number of sustainable fishing and the total allowable catches in the waters of Pasuruan, East Java: to know the status of fishery resources utilization, and to construct management strategis for fishery resources management in the waters of Pasuruan, East Java. Calculation of Maximum Sustainable Yiled (MSY) and the Total Allowable Catch (JTB) applied by Schaefer and fox methods. The result showed that MSY calculation models fox was 9419.86 tonnes, which JTB was 7535.89. The level of fisheries utilization in the waters of Pasuruan, East Java, categorizeas overexploited. Most respondent in the FGD activity (81.74%) agree that strategies of fisheries resources utilization in the waters of Pasuruan, East Java was the strategy of fishing operation based on fishing ground fishing season.